Triterpene-enriched extracts from Ganoderma lucidum inhibit growth of hepatoma cells via suppressing protein kinase C, activating mitogen-activated protein kinases and G2-phase cell cycle arrest - Lin, Shwu-Bin; Li, Chyi-Hann; Lee, Shiuh-Sheng; Kan, Lou-Sing (Life sciences (1973), 2003)
The medicinal mushroom Ganoderma lucidum (G. lucidum) has been used in the Orient for the prevention and treatment of various diseases including cancer. Except for the immune enhancing properties of its polysaccharide constituent, very little is known about the anticancer activity of another major constituent, triterpenes. In this report, we studied the anticancer mechanism of triterpene-enriched extracts from G. lucidum. The triterpene-enriched fraction, WEES-G6, was prepared from mycelia of G. lucidum by sequential hot water extraction, removal of ethanol-insoluble polysaccharides and then gel-filtration chromatography. We found that WEES-G6 inhibited growth of human hepatoma Huh-7 cells, but not Chang liver cells, a normal human liver cell line. Treatment with WEES-G6 caused a rapid decrease in the activity of cell growth regulative protein, PKC, and the activation of JNK and p38 MAP kinases. The changes in these molecules resulted in a prolonged G2 cell cycle phase and strong growth inhibition. None of these effects were seen in the normal liver cells. Our findings suggest that the triterpenes contained in G. lucidum are potential anticancer agents.